Basal total testosterone serum levels predict biopsy and pathological ISUP grade group in a large cohort of Caucasian prostate cancer patients who underwent radical prostatectomy. (June 2020) - Tafuri, Alessandro; Sebben, Marco; Rizzetto, Riccardo; Amigoni, Nelia; Shakir, Aliasger; Processali, Tania; Pirozzi, Marco; Gozzo, Alessandra; Odorizzi, Katia; De Michele, Mario; Gallina, Sebastian; Bianchi, Alberto; et al.
Aims: The study aimed to evaluate associations of preoperative total testosterone (TT) with the risk of aggressive prostate cancer (PCA). Materials & methods: From 2014 to 2018, basal TT levels were measured in 726 consecutive PCA patients. Patients were classified according to the International Society of Urologic Pathology (ISUP) system. Aggressive PCA was defined by the detection of ISUP > 2 in the surgical specimen. The logistic regression model evaluated the association of TT and other clinical factors with aggressive PCA. Results: On univariate analysis, there was a significant association of basal TT with the risk of aggressive PCA as well as age, prostate-specific antigen (PSA), percentage of biopsy positive cores (BPC), tumor clinical stage (cT), and biopsy ISUP grade groups. On multivariate analysis, two models were considered. The first (model I) excluded biopsy ISUP grading groups and the second (model II) included biopsy ISUP grade groups. Multivariate model I, revealed TT as well as all other variables, was an independent predictor of the risk of aggressive disease [odds ratio (OR) = 1.585; 95% confidence interval (CI): 1.113–2.256; p  = 0.011]. Elevated basal PSA greater than 20 µg/dl was associated with the risk of aggressive PCA. Multivariate model II revealed that basal TT levels maintain a positive association between aggressive PCA, whereas age, BPC, and clinical stage cT3 lost significance. In the final adjusted model, the level of risk of TT did not change from univariate analysis (OR = 1.525; 95% CI: 1.035–2.245; p  = 0.011). Conclusion: Elevated preoperative TT levels are associated with the risk of aggressive PCA in the surgical specimen. TT may identify patients who are at risk of aggressive PCA in the low and intermediate European Association of Urology (EAU) risk classes.